Economics of the law : a primer - Weigel, Wolfgang (Routledge advanced texts in economics and finance., 2008)
There is an ever-increasing interest in the question of how and why legal norms can effectively guide human action. This compact volume demonstrates how economic tools can be used to examine this question and scrutinize these legal norms. Indeed, this is one of the first text to be based on civil law instead of the more usual common law, situating the study of both private and public law within the framework of institutional economics, with recommendations for further reading and a list of key terms in each chapter. Besides the standard economic problems in property, tort, contract, crime and litigation, areas covered include: new institutional economics public choice constitutional law public administrations regulatory impact analysis. This book is essential reading for students in law schools and economics departments alike, particularly those engaged with the methodology of law and economics, applied economics and economic methods of legal policy.